Architectural conservation, Bangladesh - Imamuddin, Abu H.; Seminar on Architectural Conservation (1993 : Dhaka, Bangladesh) (Dhaka, Bangladesh : Asiatic Society of Bangladesh : Distributor, Academic Publishers, 1993)
Proceedings of the Seminar on Architectural Conservation, held at Dhaka, Bangladesh, April 17, 1993.
Includes bibliographical references and index.
Keywords: Architecture -- Conservation and restoration -- Bangladesh -- Congresses